2023
DOI: 10.3390/plants12193357
|View full text |Cite
|
Sign up to set email alerts
|

Gene Co-Expression Analysis Reveals the Transcriptome Changes and Hub Genes of Fructan Metabolism in Garlic under Drought Stress

Qianyi Zhou,
Haihong Sun,
Guoli Zhang
et al.

Abstract: Drought has become a serious environmental factor that affects the growth and yield of plants. Fructan, as an important storage compound in garlic, plays an important role in drought tolerance. Genomic changes in plants under drought stress clarify the molecular mechanism of plants’ responses to stress. Therefore, we used RNA-seq to determine the transcriptomic changes in garlic under drought stress and identified the key module related to fructan metabolism by weighted gene co-expression network analysis. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Protection from stress-related effects is facilitated by changes in the content of hexoses through hydrolysis of sucrose by all invertases and fructans by acid invertases and FEHs [14,15]. Consistent with these data, transcriptomic analyses indicate that the adaptive response of garlic under salt stress includes regulation of sucrose metabolism [27,28] and that fructans, which along with sucrose are important storage sugars, can stimulate garlic resistance to low temperatures [26] and drought [29].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Protection from stress-related effects is facilitated by changes in the content of hexoses through hydrolysis of sucrose by all invertases and fructans by acid invertases and FEHs [14,15]. Consistent with these data, transcriptomic analyses indicate that the adaptive response of garlic under salt stress includes regulation of sucrose metabolism [27,28] and that fructans, which along with sucrose are important storage sugars, can stimulate garlic resistance to low temperatures [26] and drought [29].…”
Section: Discussionmentioning
confidence: 63%
“…Garlic (Allium sativum L.) is a popular spice plant with considerable medicinal properties due to the presence of a large number of biologically active compounds with beneficial health effects [21]; it is also used to improve soil quality through intercropping and crop rotation [22]. Garlic is cultivated all over the world, which, given its non-sexual reproduction, suggests high adaptive plasticity of the genome and a well-developed stress response system [23][24][25]; it is known to be sensitive to various abiotic stresses, including low temperatures [26], soil salinity [27,28], and drought [29]. Transcriptomic and metabolomic studies have revealed that stresses affect the metabolism of sucrose and fructans, which contribute to garlic yield and quality [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such conditions facilitate the accumulation of carbohydrates, particularly affecting carbohydrate metabolism pathways in garlic. A preceding study reported that garlic mitigates oxidative damage from drought stress primarily through the induction of fructan synthesis and catabolism, with noted fluctuations in fructan levels initially increasing and subsequently decreasing [ 54 ]. The degradation and synthesis of fructans are related to FEH, 1-fructosyltransferase (1-FFT), and sucrose 1-fructosyltransferase (1-SST).…”
Section: Resultsmentioning
confidence: 99%